STUDY LITERATURE: FACTORS ASSOCIATED WITH PERSONAL HYGIENE MENSTRUATION IN ADOLESCENTS WITH MENTAL RETARDATION - Amalia Rizqi Sholihah; Restuning Widiasih; Tetti Solehati (Journal of Maternity Care and Reproductive Health, 2020)
Menstruation is experienced by every young woman, both young women with special needs and normal young women. In young women with mental retardation, they have limitations in doing menstrual personal hygiene, they may need help and guidance from parents. This literature review aimed to find out factors related to doing menstrual personal hygiene in adolescent girls with mental retardation. The databases were Google Scholar and Pubmed. Keywords in Indonesian and English included factors, menstrual personal hygiene, and mental retardation. The search results found 175 articles. The inclusion criteria used were full text published articles, in the period 2010 - 2019, the article discussed menstrual personal hygiene in adolescents with mental retardation. Based on the inclusion criteria, 9 articles were found that met the review requirements. The results of the analysis identified that there were two factors related to menstrual personal hygiene in young women, including internal factors: knowledge, classification of mental retardation, and external factors which are parental support, parental education level, and parenting. Internal factors have a significant relationship with adolescent girls when performing menstrual personal hygiene. Further research on the experience of adolescents with mental retardation is needed to see the readiness of adolescents in the face of menstruation.Keywords: Adolescent girls, factors, menstruation, personal hygiene, mental retardation.